Mental stress among patients undergoing orthodontic treatment during coronavirus-19 global pandemic - Sherchan, Prabesh; Gurung, Deepa; Bogati, Subekshya; Gupta, Sujaya (Journal of Kathmandu Medical College, 2022)
Background: Coronavirus disease 2019 (COVID-19) is the most recent disease of corona virus family that impacted people all over the world. Subsequent lockdown and fear of disease transmission greatly affected the orthodontic appointments, treatments, as well as mental health. Objectives: To assess the mental stress among patients undergoing orthodontic patients during COVID-19 pandemic. Methods: A descriptive cross-sectional study was conducted among individuals undergoing orthodontic treatment in the department of Orthodontics and Dentofacial Orthopaedics in Dental Hospital of Kathmandu Medical College from 2020 December to 2021 February after institutional ethical approval. Data were collected from 108 participants by convenience sampling technique using questionnaire. Exclusion criteria included patients who answered <75% questions and those who did not sign the informed consent form. Data were analysed for descriptive statistics in SPSS v.22. Results: Among all 108 patients, nine (8.3%) were very much worried that COVID-19 outbreak might cause teeth not to move as expected and 40 (37.1%) participants were very much depressed. Regarding perception of individuals concerning COVID-19 pandemic, 44 (40.7%) participants thought they had adequate knowledge about COVID-19. Almost half (48, 44.4%) patients in this study felt very much nervous that nothing could calm them. When participants were asked what were their main concerns for COVID-19 outbreak, more than half (60, 55.6%) responded risk of infection and 71 (65.7%) reported the impact on their work or study as their main concerns. Conclusion: As Orthodontists we must be aware of similar threats in future and take measures to improve the accessibility to dental practice.